Psychiatric disorders and urbanization in Germany - Koelen Jurrijn; Peen Jaap; Dekker Jack; Smit Filip; Schoevers Robert (BMC, 2008)
Abstract Background Epidemiological studies over the last decade have supplied growing evidence of an association between urbanization and the prevalence of psychiatric disorders. Our aim was to examine the link between levels of urbanization and 12-month prevalence rates of psychiatric disorders in a nationwide German population study, controlling for other known risk factors such as gender, social class, marital status and the interaction variables of these factors with urbanization. Methods The Munich Composite International Diagnostic Interview (M-CIDI) was used to assess the prevalence of mental disorders (DSM-IV) in a representative sample of the German population (N = 4181, age: 18-65). The sample contains five levels of urbanization based on residence location. The epidemiological study was commissioned by the German Ministry of Research, Education and Science (BMBF) and approved by the relevant Institutional Review Board and ethics committee. Written informed consent was obtained for both surveys (core survey and Mental Health Supplement). Subjects did not get any financial compensation for their study participation. Results Higher levels of urbanization were linked to higher 12-month prevalence rates for almost all major psychiatric disorders (with the exception of substance abuse and psychotic disorders). The weighted prevalence percentages were highest in the most urbanized category. Alongside urbanization, female gender, lower social class and being unmarried were generally found to be associated with higher levels of psychopathology. The impact of urbanization on mental health was about equal (for almost all major psychiatric disorders) in young people and elderly people, men and women, and in married and single people. Only people from a low social class in the most urbanized settings had more somatoform disorders, and unmarried people in the most urbanized settings had more anxiety disorders. Conclusion Psychiatric disorders are more prevalent among the inhabitants of more urbanized areas. probably because of environmental stressors.